Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T16:15:00+02:00
A) 3(5a+3b)-(10a+10b) dla a=-½, b=0,2
3(5*(-1/2) + 3*0,2) - (10*(-1/2)+10*0,2)=
3(-2,5 + 0,6) - (-5+2)=
-7,5 + 1,8 + 5 - 2 = -2,7

b) 2-10(2y-x)+2(-y+4x) dla x=-1, y=-0,1
2-10(2*(-0,1 + 1)+2(0,1 -4)=
2-10(-0,2 + 2) + 0,2 - 8=
2 - 2 + 20 + 0,2 - 8 = 12,02

c)-2(-3x-y)-3x(1+y) dla x=2, y=¼
-2(-6 - 1/4) -6(1+1/4)=
12 + 1/2 -6 - 1,5 = 5

d)-(6-3y)-(x-2y)-2(x+y) dla x=-1, y=-⅓
-(6-3*(-1/3) - (-1 -2*(-1/3)-2(-1+(-1/3)=
-(7 -(-1 + 2/3) -2(-1 1/3)=
-(7 +1 - 2/3 + 2 2/3)=
-7 -1 +2/3 -2 2/3= -10